ESENSI BAHASA DI TINJAU DALAM FILSAFAT BAHASA - Ria Fitriani (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2023)
Philosophy can be studied through 3 aspects, namely Ontology, Epistemology and Axiology. In contrast to other branches of philosophy, the philosophy of language is a complex field and it is difficult to determine the scope of understanding (Devitt, 1987). However, this does not mean that the philosophy of language is a field of philosophy whose object of discussion is not clear. Philosophy of language, like other philosophical fields, such as legal philosophy, human philosophy, natural philosophy, social philosophy and other philosophical fields, discusses, analyzes and searches for the nature of language as a material object of language philosophy (Davis, 1976). This understanding must be distinguished from the understanding of the analytic philosophy of language which uses language as a tool for analyzing philosophical concepts and problems. Therefore, the philosophy of language in this sense discusses language as a material object of philosophy, so that the philosophy of language discusses the nature of language itself.